Shared decision-making and specific informed consent in patients with aortic aneurysms - Marcela Juliano Silva Cunha; Marcelo Passos Teivelis; Cynthia de Almeida Mendes; Conrado Dias Pacheco Annicchino Baptistella; Pedro Vasconcelos Henry Sant´Anna; Nelson Wolosker (Einstein (São Paulo), 2023)
ABSTRACT Objective To analyze the refusal rate of elective aortic aneurysm surgery in asymptomatic patients after the presentation of a detailed informed consent form followed by a meeting where patient and their families can analyze each item. Methods We conducted a retrospective analysis of 49 patients who had aneurysms and were offered surgical treatment between June 2017 and February 2019. The patients were divided into two groups: the Rejected Surgery Group, which was composed of patients who refused the proposed surgical treatment, and the Accepted Surgery Group, comprising patients who accepted the proposed surgeries and subsequently underwent them. Results Of the 49 patients, 13 (26.5%) refused surgery after reading the informed consent and attending the comprehensive meeting. We observed that patients who refused surgery had statistically smaller aneurysms than those who accepted surgery (9% versus 26%). These smaller aneurysms were above the indication size, according to the literature. Conclusion One-quarter of patients who were indicated for elective surgical repair of aortic aneurysms rejected surgery after shared decision-making, which involved presenting patients with an informed consent form followed by a clarification meeting for them and their families to analyze each item. The only factor that significantly influenced a rejection of the procedure was the size of the aneurysm; patients who rejected surgery had smaller aneurysms than those who accepted surgery.